Decentralization and Participatory Rural Development: A Literature Review - Muhammad Shakil Ahmad; Noraini Bt. Abu Talib (Contemporary Economics)
Most of the developing nations are still struggling for efficient use of their resources. In order to overcome physical and administrative constraints of the development, it is necessary to transfer the power from the central government to local authorities. Distribution of power from improves the management of resources and community participation which is considered key to sustainable development. Advocates of decentralization argue that decentralized government is source to improve community participation in rural development. Decentralized government is considered more responsive towards local needs and development of poor peoples. There are many obstacles to expand the citizen participation in rural areas. There are many approaches for participatory development but all have to face the same challenges. Current paper highlights the literature about Decentralization and participatory rural development. Concept and modalities of Decentralization, dimensions of participation, types of rural participation and obstacles to participation are also the part of this paper.